YANGTZIRAMULUS ZHANGI NEW GENUS AND SPECIES, A CARBONATE-HOSTED MACROFOSSIL FROM THE EDIACARAN DENGYING FORMATION IN THE YANGTZE GORGES AREA, SOUTH CHINA - Shen, Bing; Xiao, Shuhai; Zhou, Chuanming; Yuan, Xunlai (PALEONTOLOGICAL SOC INC, 2009)
Very few macroscopic Soft-bodied Ediacaran fossils are hosted in carbonates: most of them are preserved as casts and molds in siliciclastic rocks or as carbonaceous compressions in black shales. This taphonomic bias limits our capability to fully understand the diversity and paleoecology of macroscopic Ediacaran life forms. Previous reports have shown that the upper Ediacaran Dengying Formation ill South China and Khatyspyt Formation in Siberia contain macroscopic soft-bodied fossils preserved in bituminous limestone thus they have the potential to expand Our knowledge about file Ediacaran biosphere. However, the biogenecity of the Dengying fossils described in Xiao et al. (2005) has been questioned. In this paper, we provide additional material and arguments In support of the biogenecity of these fossils, which are formally described as Yangtziramulus zhangi new genus and species. Yangtziramulus zhangi consists of a branching system with a central axis and tubes oil both sides. The tubes appear to be distally open. Yangtziramulus zhangi is interpreted as a flat-lying benthic organism, as indicated by the Mutual avoidance relationship among densely clustered individuals. Yangtziramulus zhangi finds few morphological analogs among modern organisms, but it is broadly similar to several macroscopic Ediacaran forms. Its morphological and ecological complexity is inconsistent with a microbial interpretation. Yangtziramulus zhangi is typically covered by it thin veneer of fine-grained silts. Suggesting that it was probably smothered and killed by an episodic flux of silty sediments (event deposits). Its tube walls are replaced with early diagenetic calcspars.